Preparation method and application of thiazole-[5, 4-d] thiazole covalent triazine polymer material

Through the preparation of thiazole-[5,4-d]thiazole covalent triazine polymer materials, the low efficiency and stability problems of porous organic polymer materials in the generation of solar steam are solved, and efficient photothermal conversion and stability are achieved. , suitable for solar water evaporation.

CN119320494AActive Publication Date: 2025-01-17NANKAI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411434907.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The existing porous organic polymer materials have problems with low efficiency and stability in the generation of solar steam, which are mainly due to their hydrophobicity and limited light absorption capacity, resulting in low photothermal conversion efficiency and complex operation.

Method used

Using the preparation method of thiazole-[5,4-d]thiazole covalent triazine polymer material, the thiazole-[5,4-d]thiazole monomer and anhydrous zinc chloride are heated under vacuum , form a material with high stability and wide sunlight absorption.

Benefits of technology

It has achieved high photothermal material with good photothermal conversion efficiency and stability. It is suitable for solar water evaporation and is simple to synthesis, and is suitable as an efficient photothermal conversion material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320494A_ABST
    Figure CN119320494A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a thiazole-[5, 4-d] thiazole covalent triazine polymer material, and belongs to the technical field of porous organic polymer materials. The preparation method of the thiazole-[5, 4-d] thiazole covalent triazine polymer material comprises the following steps: uniformly mixing a monomer and anhydrous zinc chloride, transferring the mixture into a glass tube, cooling liquid nitrogen, and carrying out melting sealing in a vacuum state; then transferring the sealed glass tube into a muffle furnace for heating reaction to obtain a product; after the reaction is finished, taking out a product, and sequentially grinding, washing and drying in vacuum to obtain the thiazole-[5, 4-d] thiazole covalent triazine polymer material. The thiazole-[5, 4-d] thiazole covalent triazine polymer material disclosed by the invention is simple to synthesize, high in yield and good in stability, has low-spin-density free radicals and hydrophilicity, is suitable for being used as a high-performance photothermal conversion material, and has a very good application prospect in the field of solar water evaporation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of porous organic polymer materials, and in particular relates to a preparation method and application of a thiazole-[5,4-d]thiazole covalent triazine polymer material. Background Art

[0002] Solar energy is a clean and renewable energy source that can be efficiently converted through photochemical, photovoltaic and photothermal processes. In the past few decades, the emergence of photothermal conversion has greatly expanded the use of solar domestic hot water, as well as water desalination or purification. Researchers are committed to achieving efficient solar steam generation, however, photobleaching and limited solar light absorption lead to low efficiency of photothermal conversion. Preparing materials with wide solar light absorption by endowing materials with free radical properties is an important strategy to achieve efficient solar steam generation. However, the inherent reactivity and strong electronic interactions of free radicals are usually accompanied by unstable problems and unpredictable properties of the aggregated state. Therefore, it remains a huge challenge to construct efficient photothermal conversion materials with highly stable and persistent organic radicals.

[0003] As a new type of polymer semiconductor, porous organic polymers (POPs) have become highly promising candidates in the field of SSG due to their advantages such as light weight, inherent porosity and low thermal conductivity. However, the inherent hydrophobicity and limited light absorption (especially in the near-infrared region) of POPs are two major bottlenecks that hinder their application in SSG. To address this problem, some post-treatments such as carbonization, hybridization, chemical hydrophilic treatment or post-synthetic modification have been carried out on POPs to enhance their light absorption capacity and hydrophilicity. However, this not only significantly complicates their operation in solar steam generation, but also reduces their long-term stability due to the delamination of substrates and photothermal materials, which complicates their application in SSG. Therefore, it is of great significance to develop a photothermal conversion material with high photothermal conversion efficiency, simple synthesis and good stability. Summary of the invention

[0004] In view of the defects and shortcomings of the prior art, the object of the present invention is to provide a preparation method and application of a thiazole-[5,4-d]thiazole covalent triazine polymer material.

[0005] In order to achieve the above-mentioned invention object, the present invention provides the following technical solutions:

[0006] The preparation method of the above-mentioned thiazole-[5,4-d]thiazole covalent triazine polymer material comprises the following steps:

[0007] 1) The thiazole-[5,4-d]thiazole monomer and anhydrous zinc chloride are uniformly mixed and transferred into a glass tube, cooled with liquid nitrogen, and then melted and sealed under vacuum;

[0008] 2) transferring the sealed glass tube to a muffle furnace for heating reaction to obtain a product;

[0009] 3) The product is taken out, ground, washed and vacuum dried to obtain a thiazole-[5,4-d]thiazole covalent triazine polymer material.

[0010] Preferably, the monomer in step 1) is prepared by the following method: dithiooxamide and 4-formylbenzonitrile are mixed and heated to carry out polycondensation reaction, thereby obtaining a thiazole-[5,4-d]thiazole monomer.

[0011] Preferably, in step 1), the molar ratio of anhydrous zinc chloride to monomer is 1-10.

[0012] Preferably, the liquid nitrogen cooling time in step 1) is 5 to 15 minutes.

[0013] Preferably, the heating rate in step 2) is 2 to 10°C / min.

[0014] Preferably, the heating temperature in step 2) is 300-500° C., and the heating time is 24-72 hours.

[0015] Preferably, the grinding method in step 3) is ball milling for 5-10 minutes.

[0016] Preferably, the washing solvents in step 3) are HCl aqueous solution, H2O, methanol and acetone, respectively.

[0017] Preferably, in step 3), the product is dried at a temperature of 60 to 80° C. during vacuum drying, and the drying time is usually 12 to 48 hours.

[0018] The thiazole-[5,4-d]thiazole covalent triazine polymer material is prepared by the preparation method.

[0019] The application of the thiazole-[5,4-d]thiazole covalent triazine polymer material includes being used as a photothermal material for solar water evaporation.

[0020] The beneficial effects of the present invention are: the thiazole-[5,4-d]thiazole covalent triazine polymer material of the present invention has high photothermal conversion efficiency, simple synthesis, good stability, is suitable as a photothermal conversion material, and has good application prospects in the field of water evaporation. Specifically:

[0021] 1) The present invention uses a high-temperature ion thermal method to prepare a black powder, which is a very potential photothermal conversion material and has the characteristics of free radicals and high stability.

[0022] 2) The present invention directly utilizes monomer trimerization to generate the target product, with simple steps and convenient synthesis.

[0023] 3) The thiazole-[5,4-d]thiazole covalent triazine polymer material of the present invention has a high light-to-heat conversion efficiency and can be used as a solar water evaporation material, with broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the infrared spectra of the monomer DTz-CN and the thiazole [5,4-d] thiazole covalent triazine polymer CTF-DTz in the example.

[0025] Figure 2 Powder X-ray diffraction spectra of DTz-CN and CTF-DTz in the examples.

[0026] Figure 3 The thermogravimetric diagrams of DTz-CN and CTF-DTz in the examples are shown in FIG.

[0027] Figure 4 It is the nitrogen adsorption-desorption isotherm of CTF-DTz in the example.

[0028] Figure 5 It is the UV-visible absorption spectrum of CTF-DTz in the embodiment.

[0029] Figure 6 It is the electron paramagnetic resonance spectrum of CTF-DTz in the embodiment.

[0030] Figure 7 This is the CTF-DTz heating curve in the embodiment.

[0031] Figure 8 This is the CTF-DTz water evaporation curve in the example. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not limited to the present invention.

[0033] Embodiment 1:

[0034] A thiazole-[5,4-d]thiazole covalent triazine polymer material, the preparation method of which comprises the following steps:

[0035] Synthesis of monomer DTz-CN: Dithiooxamide (600.99 mg, 5 mmol) was added to a nitrobenzene suspension (100 mL) of 4-formylbenzonitrile (1.31 g, 10 mmol) and heated at 130 ° C overnight. The resulting mixture was cooled to room temperature, and ether was added to form a red solid, which was filtered and washed with Et2O without further purification. Since the compound is insoluble in water, NMR and HRMS cannot be determined.

[0036] The synthetic reaction formula of monomer DTz-CN is as follows:

[0037]

[0038] Synthesis of Thiazole-[5,4-d] Thiazole Covalent Triazine Polymer CTF-DTz: DTz-CN (344.4 mg, 1 mmol) and ZnCl2 (680 mg, 5.0 mmol, 5 eq) were uniformly mixed and transferred to a glass tube (1×14 cm). After cooling with liquid nitrogen for 5 min, the tube was melt-sealed under vacuum. The sealed glass tube was then transferred to a muffle furnace for heating reaction. The heating program was: 5°C / min, 400°C, 40 h. After the reaction was completed, it was cooled to room temperature. The cooled sample was taken out and ground, and washed with 2M HCl (5×100 mL), H2O (5×100 mL), methanol (3×50 mL) and acetone (1×50 mL). The washed sample was placed in a vacuum drying oven and dried at 60°C for 12 h to obtain a dark powder.

[0039] The synthesis reaction formula of thiazole-[5,4-d]thiazole covalent triazine polymer CTF-DTz is as follows:

[0040]

[0041] Performance Testing:

[0042] 1) The infrared spectra of DTz-CN and CTF-DTz are as follows Figure 1 shown.

[0043] Depend on Figure 1 It can be seen that: 2233cm -1 The disappearance of the nitrile bond at 1580 cm -1 The appearance of a strong absorption band at indicates the formation of a triazine ring, indicating that the nitrile group was successfully converted into a triazine structure through trimerization, i.e., the generation of CTF-DTz.

[0044] 2) Powder X-ray diffraction spectra of DTz-CN and CTF-DTz are as follows: Figure 2 shown.

[0045] Depend on Figure 2 It can be seen that the diffraction peak of CTF-DTz formed after cyano trimerization was observed experimentally at a 2θ value of 25°, and this peak value confirmed the formation of the crystalline nature of CTF-DTz.

[0046] 3) Thermogravimetric images of DTz-CN and CTF-DTz are shown in Figure 3 shown.

[0047] Depend on Figure 3It can be seen that DTz-CTF still maintains 90% of its initial weight at 606°C in a nitrogen atmosphere, indicating that it has high thermal stability.

[0048] 4) Nitrogen adsorption-desorption isotherms of CTF-DTz Figure 4 shown.

[0049] Depend on Figure 4 It can be seen that the adsorption isotherm of CTF-DTz shows typical type I characteristics, with sharp N2 uptake in the low relative pressure region (P / P0<0.05), indicating microporous properties. The Brunauer-Emmett-Teller (BET) surface area of ​​DTz-CTF is 1061.5 m 2 / g. The gas adsorption curves of the samples before and after illumination are basically the same, indicating that the porosity remains basically unchanged and the structural stability is very good.

[0050] 5) UV-visible absorption spectrum of CTF-DTz Figure 5 shown.

[0051] Depend on Figure 5 It can be seen that CTF-DTz exhibits a strong and extended absorption spectrum in the range of 300-2500nm. The broadening and strong absorption are likely to come from the low band gap of the π-π conjugated structure and its spatial interaction.

[0052] 6) CTF-DTz electron spin resonance spectrum Figure 6 shown.

[0053] Depend on Figure 6 It can be seen that CTF-DTz has a significant ESR signal at G factor = 2.003, indicating the generation of carbon radicals. Temperature-dependent ESR measurements from 195K to 275K show that the peak-to-peak height in CTF-DTz increases with increasing temperature, indicating an increase in spin parallelism, which is a characteristic of localized radicals with weak spin-spin interactions.

[0054] 7) CTF-DTz heating curve is as follows Figure 7 shown.

[0055] Depend on Figure 7 It can be seen that CTF-DTz heats up rapidly after being irradiated by a laser with a wavelength of 808nm, and the temperature rise varies with the power of the laser lamp. 2 The sample was heated to 220 °C under laser irradiation.

[0056] 8) CTF-DTz water evaporation curve Figure 8 shown.

[0057] Depend on Figure 8It can be seen that the mass of water in the beaker where CTF-DTz is located decreases after 1 h of illumination. By calculation, the water evaporation rate can be obtained to be 2.0 kg m -2 h -1 , the solar energy conversion efficiency is as high as 99.4%.

[0058] Embodiment 2:

[0059] Different from Example 1, in this example, 1 mmol of DTz-CN and 5.0 mmol of ZnCl2 are uniformly mixed, transferred to a glass tube, cooled with liquid nitrogen for 5 minutes, and then melt-sealed under vacuum. The sealed glass tube is transferred to a muffle furnace for heating reaction, and the heating program is: 5°C / min, 400°C, 40h. After the reaction is completed, it is cooled to room temperature. The cooled sample is taken out and ground, and washed with 2M HCl (5×100mL), H2O (5×100mL), methanol (3×50mL) and acetone (1×50mL). The washed sample is placed in a vacuum drying oven and dried at 60°C for 12h to obtain a dark powder.

[0060] Embodiment 3:

[0061] Different from Examples 1 and 2, in this example, 1 mmol of DTz-CN and 10 mmol of ZnCl2 are uniformly mixed, transferred to a glass tube, cooled with liquid nitrogen for 15 minutes, and then melt-sealed under vacuum. The sealed glass tube is transferred to a muffle furnace for heating reaction, and the heating program is: 2°C / min, 500°C, 72h. After the reaction is completed, it is cooled to room temperature. The cooled sample is taken out and ground, and washed with 2M HCl (5×100mL), H2O (5×100mL), methanol (3×50mL) and acetone (1×50mL). The washed sample is placed in a vacuum drying oven and dried at 70°C for 48h to obtain a dark powder.

[0062] Embodiment 4:

[0063] Different from Examples 1-3, in this example, 1 mmol of DTz-CN and 8.0 mmol of ZnCl2 are uniformly mixed, transferred to a glass tube, cooled with liquid nitrogen for 8 minutes, and then melt-sealed under vacuum. The sealed glass tube is transferred to a muffle furnace for heating reaction, and the heating program is: 10°C / min, 300°C, 24h. After the reaction is completed, cool to room temperature. The cooled sample is taken out and ground, and washed with 2M HCl (5×100mL), H2O (5×100mL), methanol (3×50mL) and acetone (1×50mL). The washed sample is placed in a vacuum drying oven and dried at 80°C for 24h to obtain a dark powder.

[0064] Embodiment 5:

[0065] Different from Examples 1-4, in this example, 1 mmol of DTz-CN and 3.0 mmol of ZnCl2 are uniformly mixed, transferred to a glass tube, cooled with liquid nitrogen for 6 minutes, and then melt-sealed under vacuum. The sealed glass tube is transferred to a muffle furnace for heating reaction, and the heating program is: 8°C / min, 350°C, 50h. After the reaction is completed, it is cooled to room temperature. The cooled sample is taken out and ground, and washed with 2M HCl (5×100mL), H2O (5×100mL), methanol (3×50mL) and acetone (1×50mL). The washed sample is placed in a vacuum drying oven and dried at 65°C for 40h to obtain a dark powder.

[0066] Embodiment 6:

[0067] Different from Examples 1-5, in this example, 1 mmol of DTz-CN and 2.0 mmol of ZnCl2 are uniformly mixed, transferred to a glass tube, cooled with liquid nitrogen for 10 min, and then melt-sealed under vacuum. The sealed glass tube is transferred to a muffle furnace for heating reaction, and the heating program is: 6°C / min, 450°C, 60h. After the reaction is completed, it is cooled to room temperature. The cooled sample is taken out and ground, and washed with 2M HCl (5×100mL), H2O (5×100mL), methanol (3×50mL) and acetone (1×50mL). The washed sample is placed in a vacuum drying oven and dried at 75°C for 30h to obtain a dark powder.

[0068] The detection results of the thiazole-[5,4-d]thiazole covalent triazine polymer CTF-DTz obtained in the above Examples 2-6 are the same as those in Example 1.

[0069] The above embodiments are only used to understand the technical solution of the present invention, and are not used to limit the protection scope of the present invention. For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solution and technical concept of the present invention, and all these changes and deformations belong to the protection scope of the claims attached to the present invention.

Claims

1. A method for preparing a thiazole-[5,4-d]thiazole covalent triazine polymer material, characterized in that: The following steps are involved: 1) The thiazole-[5,4-d]thiazole monomer and anhydrous zinc chloride are uniformly mixed and transferred into a glass tube, cooled with liquid nitrogen, and then melted and sealed under vacuum; 2) transferring the sealed glass tube to a muffle furnace for heating reaction to obtain a product; 3) The product is taken out, ground, washed and vacuum dried to obtain a thiazole-[5,4-d]thiazole covalent triazine polymer material.

2. The method for preparing a thiazole-[5,4-d]thiazole covalent triazine polymer material according to claim 1, characterized in that: Step 1) The monomer is prepared by the following method: dithiooxamide and 4-formylbenzonitrile are mixed and heated for polycondensation to obtain a thiazole-[5,4-d]thiazole monomer; wherein the heating condition is 130° C., the obtained mixture is cooled to room temperature, ether is added to form a red solid, and the solid is filtered and washed with Et2O without further purification.

3. The method for preparing a thiazole-[5,4-d]thiazole covalent triazine polymer material according to claim 1, characterized in that: In step 1), the molar ratio of anhydrous zinc chloride to monomer is 1 to 10.

4. The method for preparing a thiazole-[5,4-d]thiazole covalent triazine polymer material according to claim 1, characterized in that: The liquid nitrogen cooling time in step 1) is 5 to 15 minutes.

5. The method for preparing a thiazole-[5,4-d]thiazole covalent triazine polymer material according to claim 1, characterized in that: Step 2) The heating temperature is 300-500° C., the heating time is 24-72 hours, and the heating rate is 2-10° C. / min.

6. The method for preparing a thiazole-[5,4-d]thiazole covalent triazine polymer material according to claim 1, characterized in that: Step 3) The grinding method is ball milling for 5-10 minutes.

7. The method for preparing a thiazole-[5,4-d]thiazole covalent triazine polymer material according to claim 1, characterized in that: Step 3) The washing solvents are HCl aqueous solution, H2O, methanol and acetone respectively.

8. The method for preparing a thiazole-[5,4-d]thiazole covalent triazine polymer material according to claim 1, characterized in that: Step 3) The drying temperature of the product during vacuum drying is 60-80° C., and the drying time is usually 12-48 hours.

9. A thiazole-[5,4-d]thiazole covalent triazine polymer material, characterized in that: The thiazole-[5,4-d]thiazole covalent triazine polymer material is prepared by the method described in any one of claims 1-8.

10. Use of the thiazole-[5,4-d]thiazole covalent triazine polymer material according to claim 9 for solar water evaporation in photothermal conversion.

Citation Information

Patent Citations

  • Preparation method of covalent triazine framework polymer under open system

    CN109517187A

  • Ternary random conjugated polymer based on 2,5-bis(2-thienyl)thiazolo[5,4-d]thiazolyl

    CN111019095A

  • Method for large-scale preparation of high-crystallization high-specific-surface-area covalent triazine framework

    CN113881041A

  • Amino-functionalized covalent triazine framework for gold recovery as well as preparation method and application of amino-functionalized covalent triazine framework

    CN115850698A

  • Polymer containing thiazolo [5, 4-D] thiazole structural unit as well as preparation method and application thereof

    CN116574257A